Q-switched ytterbium-doped fiber laser using V2O5 polymer film as saturable absorber - Jannifar, A.; Baharom, Mohd Faizal; Jufriadi, -; Harun, Sulaiman Wadi (Old City Publishing, 2018)
A Q-switched Ytterbium doped fiber laser (YDFL) with a Vanadium oxides (V2O5) saturable absorber (SA) is used to demonstrate the generation of pulses in the 1 micron region. V2O5 compound purified from ammonium metavanadate was embedded into poly ethylene glycol (PEO) film to function as a SA. The proposed YDFL has a Q-switching threshold of approximately 96.1 mW, and can generate pulses with repetition rate and pulse width of approximately 43.57 kHz and 2.97 µs, as well as an average output power of 2.58 mW and a pulse energy of 0.59 nJ at its highest pump power of 171.8 mW. This is the first time, to the authors’ knowledge, that a V2O5 based SA has been used to generate pulses in the 1 micron region with a YDFL.